EMG biofeedback combined with rehabilitation training may be the best physical therapy for improving upper limb motor function and relieving pain in patients with the post-stroke shoulder-hand syndrome: A Bayesian network meta-analysis - Feng, Sisi; Tang, Mingzhi; Huang, Gan; Wang, JuMei; He, Sijin; Liu, Duo; Gu, LiHua (Frontiers in Neurology, 2023)
Background: Post-stroke shoulder-hand syndrome (SHS), although not a life-threatening condition, maybe the most distressing and disabling problem for stroke survivors.Thus, it is essential to identify effective treatment strategies. Physical therapy is used as a first-line option for treating SHS; however, it is unclear which treatment option is preferred, which creates confusion in guiding clinical practice. Our study aims to guide clinical treatment by identifying the most effective physical therapy interventions for improving clinical symptoms in post-stroke SHS patients using Bayesian network meta-analysis. Methods: We conducted a systematic and comprehensive search of data from randomized controlled trials using physical therapy in patients with SHS from database inception to July 1, 2022. Fugl-Meyer Upper Extremity Motor Function Scale (FMA-UE) and Pain visual analog score (VAS) were used as primary and secondary outcome indicators. R software, version (4.1.3) and STATA software (version 16.0) were used to analyze the data. Results: A total of 45 RCTs with 3379 subjects were included, and the intervention efficacy of 7 physical factor therapies (PFT) combined with rehabilitation training (RT) were explored. Compared with the control group, all the PFT + RT included were of statistical benefit in improving limb motor function and pain relief. Also, our study indicated that EMG biofeedback combined with RT (BFT + RT) (the surface under the cumulative ranking curve (SUCRA) = 96.8%) might be the best choice for post-stroke SHS patients. Conclusion: EMG biofeedback combined with rehabilitation training may be the best physical therapy for improving upper limb motor function and relieving pain in patients with the post-stroke shoulder-hand syndrome according to our Bayesian network meta-analysis results. However, the above conclusions need further analyzed and validated by more high-quality RCTs.